Improved Performance of AlGaInP Red Micro Light-Emitting Diodes by Sidewall Treatments of Citric Acid - Zhen-Jin Wang; Xin-Liang Ye; Chih-Chiang Yang; Wei-Chen Tu; Yan-Kuin Su (IEEE Photonics Journal, 2024)
The efficiency of AlGaInP micro light-emitting diodes (micro-LEDs) was far weaker than that of GaN-based micro-LEDs in structure and performance. Consequently, there was an urgent demand to enhance their efficiency. In this study, a citric acid treatment strategy is proposed to improve the efficiency of red micro-LEDs, and the etching uniformity of different concentrations was first confirmed. We optimized the concentration of citric acid to 1:1 and modulated the wet etching time at 0, 30, 60, 90, and 120 s to treat the sidewalls of devices. Under an injection current density of 68 nA/cm2, the forward voltage (Vf) of micro-LEDs after soaking in citric acid ranged from 1.40 to 1.45 V. Compared with the sample operated at the forward voltage without citric acid sidewall treatment, AlGaInP micro-LEDs displayed significantly enhanced forward voltage. This indicates that citric acid effectively removed N-GaAs without damaging the electrical properties of the devices. Among all citric acid-treated micro-LEDs, the sample with a 60 s wet etching process showed the best improvement, with the light output power and external quantum efficiency (EQE) increased by 31.08% and 5.4%, respectively. Our proposed method to treat AlGaInP micro-LEDs presents promising opportunities for the future development of high-performance optoelectronics.